Eficiência de uso de fósforo em genótipos de meloeiro - Nascimento, Louize (2020)
The establishment of breeding programs in melon in order to improve the phosphorus use efficiency is important to reduce the use of phosphate fertilizers and minimize the environmental and economic effects of agriculture. The objective of this work was to determine the efficiency of phosphorus use of melon genotypes cultivated in hydroponic system. The experiment was carried out in a greenhouse at the Federal Rural University of Semi-Arid, in Mossoró, Rio Grande do Norte. Evaluating 10 melon genotypes, five of which are improved cultivars (vereda, gaúcho redondo conesul (GRC), amarillo canário (Aca), gaúcho casca de carvalho (GCC) e trinity) and trinity) and five unimproved (A-02, A-16, A -29, A-50 and A-52), which were submitted to two nutrient solutions (S1 - nutrient solution without phosphorus restriction (P +) and S2- nutrient solution with phosphorus restriction (P-)). The experimental design adopted was in randomized blocks, in a 10 x 2 factorial scheme, totaling 20 treatments, with five replications. Each experimental unit was represented by a plastic pot containing 8.0 L of nutrient solution and a plant in each pot. Plants were evaluated, at 19 days after transplanting, for leaf number (NFO), stem diameter (DCA), length of the main branch (CRP), length of the root system (CSR), volume of the root system (VSR ), chlorophyll (CLO), ratio of phosphorus content in the root and aerial part P(R/A), total phosphorus (PTO), dry matter ratio in the root and aerial part MS(R/A) and total dry matter (MST). Phosphorus Efficiency (EUP), Phosphorus Acquisition (EAP) and Internal Phosphorus Use (EUTP) were also verified. The data were subjected to analysis of variance (ANOVA) and, then, the grouping of means was performed by the Scott Knott test, where significant responses were obtained. In order to have a better view of the variability between the genotypes, the hierarchical grouping was performed by the UPGMA method from the Mahalanobis distances. The genotypes were classified into groups: Efficient and Responsive (ER), Inefficient and Responsive (IR), Efficient and Non-Responsive (ENR) and Inefficient and Non-Responsive (INR). The analyzes revealed the existence of genetic variability among the genotypes for the aerial part, root system, phosphorus and dry matter variables in the solution without phosphorus restriction (P +) and solution with phosphorus restriction (P-). The P-solution affected plant growth in all genotypes, causing a reduction in NFO, DCA, CRP, VSR, PTO and MST, regardless of the genotype, with the largest reductions observed for MST, PTO, CRP, NFO and VSR, obtaining losses of 77.3; 70.5; 64.8; 60.0 and 47.7%, respectively. On the other hand, the variables CSR, P(R/A) and MS(R / A) were higher in plants in P- solution, with an increase of 50.0; 45.2 and 100%, for CSR, P(R/A) and MS(R/A), respectively. Thus, it is observed that there was an increase in CSR and a reduction in VRS when there is less phosphorus availability. However, CLO was not affected by the of phosphorus effect, since the averages estimated in solutions with and without phosphorus restriction do not differ by the Student's t test (p> 0.05). Higher EUP and EUTP were found in the solution with less phosphorus availability (P-), while the highest EAP was observed in the solution P+. Regarding the EUP, the genotypes, 'GCC' and A-29, were the most efficient in the P+ solution. In situations of low phosphorus content (P-), 'trinity', A-02, A-16, A-29, A-50 and A-52 were the most efficient. Concerning the EAP, in the P + solution, the genotypes ‘vereda’, ‘Aca’, ‘GCC’, ‘trinity’, A-29 and A-52 stood out. In the P- solution, only the 'vereda' stood out. The most efficient genotypes in the EUTP, in the P + solution, were the genotypes 'GCC' and A29, while with less availability, 'trinity', A-02, A-29 and A-52. The genotypes A-16, A-29, A-50, A-52 and ‘trinity’ were classified as efficient and responsive (ER) in the solution with less phosphorus availability